Enhancing conceptual understanding of corporate finance through simulated data: a teaching and learning approach - Zakaria, Shahsuzan; Abdul Aziz, Nor Farradila; Mohd Rashid, Siti Norbaya; Mohd Ruslan, Rafiatul Adlin; Kamarudin, Mohd Faizal (GADING Journal for the Social Sciences, 2025)
This paper proposes and details a pedagogical framework that highlights the integration of simulated financial data to improve conceptual understanding and decision-making skills of Corporate Finance education. Traditional lecture-based teaching often struggles to contextualize abstract financial concepts such as Net Present Value (NPV), Internal Rate of Return (IRR), capital budgeting, capital structure, and dividend policy. Through a structured simulation framework, this study presents a novel method to bridge theoretical knowledge with practical financial scenarios. A sample capital budgeting simulation is presented as a teaching tool for implementation by educators. The paper concludes with a discussion of the implications for curriculum design, student engagement, and future research opportunities in finance education.